From Education to Food Security: A Capability-Based Perspective on Household Well-being in Indonesia - Pattinasarany, Indera Ratna Irawati (Technium Education and Humanities, 2025)
This study investigates the role of household head education in reducing the likelihood of moderate or severe food insecurity in Indonesia, drawing on Sen’s Capability Approach. Rather than treating education as a proxy for income, it is conceptualized as a foundational capability that enhances agency, access to information, and household resilience. Using nationally representative data from the Indonesian National Socioeconomic Survey (SUSENAS, 2019–2023), the study employs multilevel mixed-effects logistic regression to assess how education interacts with district-level Human Development Index (HDI) and poverty rates in shaping food security outcomes. Results confirm that higher educational attainment significantly lowers the odds of food insecurity. However, this protective effect varies by context. Education is most effective in lower-HDI districts, where institutional supports are weaker and individual agency becomes critical. In contrast, its impact diminishes in high-HDI urban areas, where high living costs and structural inequality constrain capability realization. Similarly, in high-poverty districts, the benefits of education are reduced by limited opportunities to convert educational capital into tangible well-being. A three-way interaction shows the greatest constraint where development and deprivation coexist. These findings highlight the need for context-sensitive policies combining educational investment with structural reforms to ensure meaningful expansion of capability and food security.